2017
DOI: 10.1515/tnsci-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic expression of CX36 protein in kainic acid kindling induced epilepsy

Abstract: Connexin (Cx) 36 is known to be a component of gap junctions, and has been suggested to play an important role in epilepsy. In order to determine dynamic changes of Cx36 protein expression in epilepsy and investigate the role of Cx36 in electroencephalographic activity and pathogenesis, we utilized kainic acid (KA) to induce epileptogenesis. We found that epileptic discharges began 71.8 ± 23.7 s after KA administration. Spike frequency and amplitude of epileptiform activity reached maximal levels at 30 ± 5.2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Gap junction that promotes synchronous firing of neurons was also suggested to play an important role in the generation of seizures. Its constructive protein Cx36 was found significantly increased hours after KA administration, then decreased days later (Wu et al, 2017 ). The accumulating evidence indicates that not only glutamate receptors, but also other various mechanisms were involved in KA-induced hyperexcitability and epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Gap junction that promotes synchronous firing of neurons was also suggested to play an important role in the generation of seizures. Its constructive protein Cx36 was found significantly increased hours after KA administration, then decreased days later (Wu et al, 2017 ). The accumulating evidence indicates that not only glutamate receptors, but also other various mechanisms were involved in KA-induced hyperexcitability and epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the depletion of ATP during brain ischemia (Sato et al, 1984 ) may cause an increase of [Mg 2+ ] i (Henrich and Buckler, 2008 ). The connection between Mg 2+ deficiency and formation of epileptic seizures is well-established (Randall et al, 1959 ; Hanna, 1961 ; Nuytten et al, 1991 ), and the role of electrical synapses and Cx36 in epilepsy is an important topic of research (Gajda et al, 2005 ; Volman et al, 2011 ; Kohmann et al, 2016 ; Wu et al, 2017 ). Furthermore, brain [Mg 2+ ] i is decreased in patients with Alzheimer's and Parkinson's disease (Durlach, 1990 ; Barbiroli et al, 1999 ), while patients with schizophrenia and traumatic brain injury show increased brain [Mg 2+ ] i (Hinsberger et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…To further understand the relationship between Cx36 and hyperactivity, we asked the reciprocal question: how does hyperactivity affect Cx36? Similar to the seizure susceptibility studies, work to identify this relationship has remained conflicting (Laura et al, 2015;Motaghi et al, 2017;Söhl et al, 2000;X. Wu et al, 2017).…”
Section: Ptz Induced Hyperactivity Causes a Regionally-specific Decrementioning
confidence: 99%
“…Previous findings are also mixed regarding how neuronal hyperactivity affects the expression of Cx36. In rodent seizure models and epilepsy patient post-mortem samples, some groups have found that Cx36 expression was increased (Collignon et al, 2006;Laura, Xóchitl, Anne, & Alberto, 2015;X. Wu, Wang, Hao, & Feng, 2017), while others found decreased Cx36 expression (Condorelli, Trovato-Salinaro, Mudo, Mirone, & Belluardo, 2003;Söhl et al, 2000) or no change (Motaghi, Sayyah, Babapour, & Mahdian, 2017).…”
Section: Introductionmentioning
confidence: 99%